Study of sans distribution function for different particles at different conditions - Ullah, A.K.M. Shafiq; Ahsan, M. H.; Ahmed, F. U.; Kamal, I. (BRAC University, 2010)
The size and shape of a particle can be found out by the analysis of form factor distributions in small angle neutron scattering. In the present work, the form factors were calculated theoretically by computer program and their plots were analyzed to find out the size and shape of the particles. The structure factor, on the other hand was found to be very useful to find out the particle separation and concentration of the particles. The structure factors were calculated for three potentials (i) Screened Coulomb Potential (ii) Hard Sphere Repulsion and (iii) Baxter Hard Sphere Model and their plots were analyzed to see the effects of structure factor on particle separation, concentration, particle charge, potential height, potential width and temperature.